Gamete donation in Spain. Is a legislative reform necessary? - Blasi Casagran, Cristina; Rabinad Lizano, Laura; Borisov, Evgeniya (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2026)
The regulation of gamete donation in Spain is currently framed within a biomedical perspective that prioritises technical and medical aspects, leaving aside social and ethical dimensions of increasing relevance. This article analyses the need for legislative reform to address existing gaps, especially in relation to donor anonymity and its implications for the rights of donorconceived individuals. Through a multidisciplinary methodology that combines legal analysis, empirical studies and comparisons with other jurisdictions in the European Union, significant shortcomings in the Spanish regulatory framework are identified, such as the lack of mechanisms to guarantee thealtruistic nature of donations, insufficient transparency in donor registries and inadequate information provided to donors and recipients. Based on empirical data and international case studies, the authors propose the abolition of donor anonymity and the creation of a centralised agency to regulate gamete donation in Spain. These reforms would align national practices with European Union human standards, improve transparency and ensure ethical practices in assisted reproduction. This paper seeks to contribute to the current debate by making concrete recommendations for a fairer and more transparent legislative framework on gamete donation in Spain.
Keywords: gamete donation; anonymity; Assisted Human Reproduction Information System; assisted reproduction; legislative reform